Industrialised house-building – development and conceptual orientation of the field. Issue 3 (13th July 2015) - Lessing, Jerker; Stehn, Lars; Ekholm, Anders
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This article aims to describe the development of industrialised house-building (IHB) to increase the understanding of the field. Design/methodology/approach – The study is based on an extensive literature study and a case study with three companies, studied between 2005 and 2013 which enabled an in-depth knowledge about the companies' development within IHB. Interviews, observations and document studies are the main sources of information in the case studies. Findings – IHB is a complex field, consisting of several constructs that need to be integrated and continuously developed. Development of structured technical building systems has been central to the development of IHB along with developed production methods and processes. The interest in organisational fit or adaptation to industrialisation and strategy concerning business, production and products is increasing. This implies that IHB needs to be managed strategically and not on a building project level. Practical implications – The article gives an orientation on how leading companies have structured and organised their work within industrialisation, giving valuable advice to practitioners with interest in the field. Originality/value – This article describes the development of IHB based on studies of literature and three Swedish IHB companies' development. This provides an aggregated view of the field's emergence and unique information about the studied companies' development.